Estudos de aplicações eletroquímicas de nanocristais semicondutores de CdTe crescidos em matrizes inorgânicas - Carvalho, Sanny Wedja Melo Machado de (2019)
In the present work, CdTe nanocrystals were synthesized on inorganic matrices of mesoporous silicas (MS) and lamellar hydroxides (HDL) with the objective of developing efficient and selective methods for the electrochemical detection of copper and ciprofloxacin (CPX). For the mesoporous samples, made through different synthesis methodologies, were evaluated the influence of the surface area, volumes and pore diameters of the silica matrices on the confinement process of the semiconductor particles and it was observed that the emission properties of CdTe (quantum dots, QD) depends on the texture properties of the silicas. For both inorganic matrices, results of absorption and emission spectroscopy, as well as high-resolution transmission electron microscopy images (HRTEM), evidenced a formation of hybrid materials containing CdTe nanocrystals. The electrochemical characterization of the chemically modified carbon electrodes (EQM) containing the compounds (EQM-MS4/QD and EQM-HDL/QD) show that the presence of CdTe nanocrystals, leads to an increase in the detection sensibility toward the studied analytes. After the optimization step, the working electrode made up using the modifier MS4/QD responded to a linear Cu2+ detection of 5.0 x 10-8 to 2.3 x 10-6 mol L-1 (R2 = 0,9974) and the calculated limit of detection (LOD) was 6.4 x 10-8 mol L-1. The method developed was efficient for the monitoring of Cu2+ in the sugarcane liquor, being compared with the outcomes from Flame atomic absorbtion spectroscopy (FAAS). The detection of CPX was made EQM-HDL/QD, with 20% of modifier, pH 6.0, BR buffer (Britton-Robinson), accumulation time of 300 s and scan rate of 20 mV s-1, in the range 2.5 x 10-8 to 1.2 x 10-5 mol L-1 (R2 = 0.9970), a sensitivity of LOD = 4.2 x 10-8 mol L-1 and limit of quantification (LOQ) of 1.3 x 10-7 mol L-1, accuracy of 3.0%, recovery of 94.0% and satisfactory selectivity in the presence of some interferents. Tests of CPX determination in commercial capsules of 500 mg of ciprofloxacin showed the applicability of the method.